Frailty assessment in adults undergoing allogeneic hematopoietic cell transplantation: insights from a multicenter GETH-TC study to optimize outcomes and care - Salas, María Queralt; Solano, María Teresa; Baile González, Mónica; Acera Gómez, Marina; Fox, Laura; Pérez Artigas, María del Mar; Santamaría, Ana; Quintela González, María del Carmen; Sánchez Salinas, Andrés; Salmerón Camacho, Joaquina M.; Illana Álvaro, Verónica; Abdallahi-Lefdil, Zahra; et al. (Frontiers in Immunology, 2025)
IntroductionThis multicenter prospective study sponsored by the Grupo Español de Transplante Hematopoyético y Terapia Celular (GETH-TC) explores the use of frailty assessments in allo-HCT candidates.MethodsFrailty was measured using the HCT Frailty Scale at first consultation and HCT admission in 404 adults from 15 HCT programs in Spain. Based on the results, patients were classified into fit, pre-frail and frail categories. Allo-HCT outcomes were analyzed according to the results obtained from the HCT Frailty Scale. Data was collected prospectively and all patients signed informed consent.ResultsAt first consultation, 102 (26.2%) patients were classified as fit, 248 (61.4%) as pre-frail, and 50 (12.4%) as frail. During the study, 62 (15.2%) patients participated in a pre-habilitation program. Among non-pre-habilitated patients (n=342), the proportion of fit patients decreased from 26.6% to 16.7%, while frail patients increased from 12.7% to 19.9%. In contrast, pre-habilitated patients (n=62) showed improvements, with fit patients increasing from 24.2% to 46.8%, and frail patients decreasing from 9.7% to 3.2%. Multivariate analysis confirmed lower OS (HR 2.52, P=0.002) and higher NRM (HR 2.69, P=0.013) in frail patients at HCT admission compared to fit ones, with a trend towards lower OS in pre-frail patients (HR 1.54, P=0.097).ConclusionThis study highlights the feasibility of incorporating the HCT Frailty Scale into clinical practice, confirms its negative impact of frailty on transplant outcomes, and suggests that frailty is dynamic and potentially reversible through pre-transplant interventions.